A Whole Food Plant-Based Diet Is Effective for Weight Loss: The Evidence. Issue 5 (September 2020) - Greger, Michael
What does the best available balance of scientific evidence show is the optimum way to lose weight? Calorie density, water content, protein source, and other components significantly influence the effectiveness of different dietary regimes for weight loss. By "walling off your calories, " preferentially deriving your macronutrients from structurally intact plant foods, some calories remain trapped within indigestible cell walls, which then blunts the glycemic impact, activates the ileal brake, and delivers prebiotics to the gut microbiome. This may help explain why the current evidence indicates that a whole food, plant-based diet achieves greater weight loss compared with other dietary interventions that do not restrict calories or mandate exercise. So, the most effective diet for weight loss appears to be the only diet shown to reverse heart disease in the majority of patients. Plant-based diets have also been found to help treat, arrest, and reverse other leading chronic diseases such as type 2 diabetes and hypertension, whereas low-carbohydrate diets have been found to impair artery function and worsen heart disease, the leading killer of men and women in the United States. A diet centered on whole plant foods appears to be a safe, simple, sustainable solution to the obesity epidemic.